RISE: Stakeholders site-level workshop for Project Ecosystem Service Assessment in the Central Forest Spine (CFS) Selangor using toolkit for Ecosystem Service Site-based Assessment (TESSA) / Ts. Dr Nor Hanisah Mohd Hashim ... [et al.] - Mohd Hashim, Nor Hanisah; Mohd Nasir, Nurul Akmaniza; Chek Sulaiman, Firdaus; Bahrain, Nawfal Kamarul (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Ecosystem service assessment in the Central Forest Spine (CFS) Selangor using TESSA Toolkit project was funded by Yayasan Hasanah with the collaboration between South East Asia Rainforest Research Partnership (SEARPP), Selangor Forestry Department and Universiti Teknologi MARA (UiTM), Shah Alam. This three-year project aims to identify and assess the ecosystem services in the ecology corridor of CFS B-SL1 Selangor: Raja Musa Forest Reserve - Gading Forest Reserve - Bukit Tarik Forest Reserve, Selangor by focusing on the three main ecosystems; climate regulation, water and nature-based recreation. This project is led by Ts. Dr Nor Hanisah Mohd Hashim, a senior lecturer from Centre of Studies for Park and Amenity Management, E Faculty of Architecture, Planning and Surveying, UiTM Shah Alam.